2014
DOI: 10.1002/lary.24764
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors of Bell's palsy: Multivariate analysis of electrophysiological findings

Abstract: 4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
35
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 51 publications
2
35
0
2
Order By: Relevance
“…Dry mouth at the onset is highly correlated with a severe grade of palsy, and when present it is related to a poor chance of recovery in the early period. This finding could be of important interest for those centers where the access to the electrophysiological testing is not easy and where the choice of referring BP patients to further examinations (EMG, EnoG, Blink Reflex) [ 27 ] and subsequent therapy (physical rehabilitation and surgical decompression) is made more difficult. This study investigated the symptoms on the basis of the patient's history only without the use of objective examinations; nevertheless, a correlation with data present in literature was found.…”
Section: Discussionmentioning
confidence: 99%
“…Dry mouth at the onset is highly correlated with a severe grade of palsy, and when present it is related to a poor chance of recovery in the early period. This finding could be of important interest for those centers where the access to the electrophysiological testing is not easy and where the choice of referring BP patients to further examinations (EMG, EnoG, Blink Reflex) [ 27 ] and subsequent therapy (physical rehabilitation and surgical decompression) is made more difficult. This study investigated the symptoms on the basis of the patient's history only without the use of objective examinations; nevertheless, a correlation with data present in literature was found.…”
Section: Discussionmentioning
confidence: 99%
“…More recent studies have found different cut‐offs to be useful. In a study of 120 subjects, Mancini and colleagues reported that amplitudes <23% of the unaffected sided were the strongest predictor of nonrecovery of normal function . Using receiver operating curve analysis, the strongest predictive values of amplitude compared with the contralateral side were 33% (67% sensitivity, 81% specificity) and 45% (100% sensitivity, 68% specificity) at baseline and second evaluations, respectively; amplitudes below these values were associated with poor prognosis.…”
Section: Facial Nervementioning
confidence: 99%
“…Findings in this group demonstrate the prognostic value of ENoG in that maximum percent degeneration reached on ENoG in the acute period after total paralysis is correlated to facial nerve function at 1 year (Table 3), in concordance with previous studies. 2,4,5,21,31 Whereas our current data series represents one of the largest studies to date in electrodiagnostic testing for acute facial paralysis, only 43% had follow-up at 1 year for assessment of long-term functional outcome, which limits the statistical power of secondary analyses investigating the prognostic value of electrodiagnostic modalities. Further, the patient cohort is highly selected based on clinical decision algorithms and referral patterns and is not likely to be reflective of all patients with acute onset of facial paralysis.…”
Section: Volitional Emg Protocolmentioning
confidence: 99%